Evidências da proteína da heterocromatina 1 (HP1) no ciclo de vida e sua interação com proteínas nucleares em cercarias de Schistosoma mansoni Schistosoma mansoni - Trindade, Natália Silva da (2020)
Schistosomiasis is a disease caused by parasites of the genus Schistosoma. It is estimated that 240 million people worldwide are infected with the parasite and about 700 million people are at risk of infection. As post-translational modifications of the stories are epigenetic mechanisms, associated with muted or active chromatin states, regulating genetic expression at the transcriptional level. Although they are as important as the post-translational modifications of the stories, studies have shown that coregulators of transcription are also important for the application of the parasite's genetic expression. Heterochromatin Protein 1 (HP1) is a known co-regulator conserved in evolution and its importance has already been detected in mammals, yeasts and protozoa, but so far in Schistosoma mansoni that has not yet been used. In this work, SmHP1 was not identified in the parasite's database and its primary amino acid structure is conserved evolutionarily. An expression of the SmHP1 mRNA was analyzed during the life cycle and a greater enclosed expression was evidenced when compared to other phases, however, an expression of the protein is not altered in all tested steps. In addition, a Western blotting analysis showed that, in the parasite's life cycle, SmHP1 can form 56kDa dimers in solution. An immunoprecipitation using the anti-HP1 antibody followed by mass spectrometry has shown that several tests of transcription of substances activated by SmHP1 are not being performed, but the maintenance roles of transcription repressants are not yet elucidated.